Hydrogen sulfide protects against cell damage through modulation of PI3K/Akt/Nrf2 signaling. (December 2019) - Zhang, Jiaxin; Shi, Chaoqun; Wang, Haochen; Gao, Cheng; Chang, Pan; Chen, Xiping; Shan, Haiyan; Zhang, Mingyang; Tao, Luyang
Graphical abstract: Highlights: Traumatic scratch injury induced ROS production and autophagic cell death in PC12 cells. Endogenous hydrogen sulfide was involved in the pathophysiology of traumatic scratch induced cell injury. Exogenous Hydrogen sulfide has yielded positive effect on traumatic scratch-mediated injury. Exogenous Hydrogen sulfide inhibited oxidative stress and autophagic cell death by modulation of the PI3K/AKT/Nrf2 pathway. Abstract: Hydrogen sulfide as the third endogenous gaseous mediator had protective effects against traumatic brain injury-induced neuronal damage in mice. However, the exact pathophysiological mechanism underlying traumatic brain injury is complicated and the protective role of H2 S is not yet fully known. Therefore, we combined the mechanical injury (scratch) with secondary injury including metabolic impairment (no glucose) together to investigate the underlying cellular mechanism of hydrogen sulfide in vitro models of traumatic brain injury. In the present study, we found that H2 S could prevent the scratch-induced decrease in the expression of cystathionine-β-synthetase, a key enzyme involved in the source of hydrogen sulfide, and endogenous hydrogen sulfide generation in PC12 cells. We also found that hydrogen sulfide could prevent scratch-induced cellular injury, alteration of mitochondrial membrane potential, intracellular accumulation of reactive oxygen species and cell death (autophagic cell death and apoptosis) in PC12 cells. It was also found that blocking PI3K/AKT pathway by LY294002, abolished the protection of H2 S against scratch-induced cellular reactive oxygen species level and NRF2 accumulation and function in the nucleus. These results suggest that hydrogen sulfide protects against cell damage induced by scratch injury through modulation of the PI3K/Akt/Nrf2 pathway. This study raises the possibility that hydrogen sulfide may have therapeutic efficacy in traumatic brain injury.